Enhancing nasopharyngeal carcinoma cell radiosensitivity by suppressing AKT/mTOR via CENP-N knockdown - Li-Zhi Wu; You Zou; Bin-Ru Wang; Hai-Feng Ni; Yong-Gang Kong; Qing-Quan Hua; Shi-Ming Chen (Journal of Translational Medicine, 2023)
Abstract Objective Investigating the impact of centromere protein N (CENP-N) on radiosensitivity of nasopharyngeal carcinoma (NPC) cells. Methods Using immunohistochemistry and immunofluorescence to detect CENP-N expression in tissues from 35 patients with radiosensitive or radioresistant NPC. Assessing the effect of combined CENP-N knockdown and radiotherapy on various cellular processes by CCK-8, colony formation, flow cytometry, and Western blotting. Establishing a NPC xenograft model. When the tumor volume reached 100 mm3, a irradiation dose of 6 Gy was given, and the effects of the combined treatment were evaluated in vivo using immunofluorescence and Western blotting techniques. Results The level of CENP-N was significantly reduced in radiosensitive tissues of NPC (p < 0.05). Knockdown of CENP-N enhanced NPC radiosensitivity, resulting in sensitizing enhancement ratios (SER) of 1.44 (5-8 F) and 1.16 (CNE-2Z). The combined treatment showed significantly higher levels of proliferation suppression, apoptosis, and G2/M phase arrest (p < 0.01) compared to either CENP-N knockdown alone or radiotherapy alone. The combined treatment group showed the highest increase in Bax and γH2AX protein levels, whereas the protein Cyclin D1 exhibited the greatest decrease (p < 0.01). However, the above changes were reversed after treatment with AKT activator SC79. In vivo, the mean volume and weight of tumors in the radiotherapy group were 182 ± 54 mm3 and 0.16 ± 0.03 g. The mean tumor volume and weight in the combined treatment group were 84 ± 42 mm3 and 0.04 ± 0.01 g. Conclusion Knockdown of CENP-N can enhance NPC radiosensitivity by inhibiting AKT/mTOR.